Aging Filipino Rice Farmers and Their Aspirations for Their Children. - Palis, Florencia G.
This study assessed the socio-demographic profile of Filipino rice farmers, their aspirations for their children, and the factors that influence such aspirations. Both quantitative and qualitative methods were used. Focus group discussions (FGDs), key informant interviews (KIIs), informal interviews, and intermittent field observations were conducted in 13 villages of 12 municipalities in three provinces of the country ? namely Agusan del Norte for Mindanao, Iloilo for the Visayas, and Isabela for Luzon. A farmer household survey was also conducted among randomly selected 923 farmers from these three provinces. The majority of the farmers did not want their children to be rice farmers. Most of them aspired to their children's college education for they want them to work on non-farming jobs in urban areas or abroad. Logistic regression showed that age and number of children of farmers increase the likelihood that a farmer aspires for at least one of his or her children to be rice farmers. On the other hand, gender, tenure, and economic status of the province decrease that likelihood. The physical and economic hardships experienced in rice farming are the major reasons farmers do not like their children to follow their steps.